Is There a Piercing of the Jurisdictional Veil? The Piercing of the Corporate Veil as an Extension of the Arbitration Agreement to Non-Signatories and as a Remedy for the Merits - Quintanilla Gutiérrez, Alejandra (2020)
In arbitration matters, one of the cases in which the effects of the arbitration agreement can be extended to a non-signatory party is through the piercing of corporate veil doctrine. The doctrine justifies the existence of such theory in order to include into the arbitration process parent or related companies that use subsidiaries as a shell to commit abuses and defraud their creditors. Moreover, corporate doctrine, no matter the jurisdictional system, establishes that the piercing of corporate veil is a remedy that applies only when the defensive separation of assets is broken and liability is assigned to a parent o related company.In this article, the author exposes the confusion related to arbitration matters in the application of the piercing of the corporate veil as a non-signatory doctrine and as a substantial remedy. Thus, it proposes a harmonization of the figure, in order to stablish a comprehensive application.